Chronic fetal hyperglycemia as a predictor of neuroendocrine imbalance development with metabolic disturbances - Kolesnik, Yu. M.; Gancheva, O. V.; Varodeeva, Yu. I.; Melnikova, O. V.; Morozova, O. V.; Колесник, Юрій Михайлович; Ганчева, Ольга Вікторівна; Вародєєва, Ю. І.; Мельникова, О. В.; Морозова, О. В.; Вародеева, Ю. И. (My University, 2013)
The aim of the research was to estimate the influence of fetal hyperglycemia on the neuroendocrine balance and the state of carbohydrate and lipid metabolism in prepubertal male rats. The research was carried out in 30 male 3 months old Wistar rats, the descendants of female rats with the experimental gestational diabetes (EGD) and 15 male Wistar rats, the descendants of female rats with normal pregnancy. In experimental animals the state of carbohydrate metabolism (the blood glucose concentration, glucose tolerance test) and lipid metabolism (the concentration of lipids, triglycerides and cholesterol in the blood plasma) was estimated. The concentration of insulin, leptin and corticosterone was also determined and the heart rate variability was analyzed. In our research the presence of neuroendocrine balance disturbances in prepubertal male rats experienced fetal hyperglycemia has been found. Hyperlipidemia, hypercholesterolemia, hypertriglyceridemia and elevation of leptin, insulin and corticosterone levels have been observed along with fasting euglycemia. The shifts of the hormonal balance revealed and indices of lipid metabolism develop simultaneously with alterations of the vegetative balance characterized by the prevalence of its sympathetic component on the background of the parasympa¬thetic part activity, which was higher than normal. It has been proven by the increase of LF/HF index by 2.4 and increase of the HF spectral capacity of the high-frequency component testifying the activity of the parasympathetic nervous system. The latter was increased by 28% (p<0.05) in comparison with the animals of the control group. The fact of neuroendocrine imbalance in the male descendants of the rats with EGD can be considered as an important prognostic sign of the metabolic disturbances development in the prepubertal period, which manifestation can be observed in adolescence with progression to old age.Метою роботи було встановлення впливу внутрішньоутробної гіперглікемії на нейроендокринний баланс та стан вуглеводного і жирового обмінів у самців щурів препубертатного віку. Дослідження було проведено на 30 3-місячних щурах-самцях лінії Вістар, нащадків самиць з експериментальним гестаційним діабетом, та 15 нащадків самок з нормальною вагітністю, у яких оцінювали стан вуглеводного (концентрація глюкози, проводився тест толерантності до глюкози) та жирового (концентрація ліпідів, тригліцеридів і холестерину) обмінів, визначали рівні гормонів інсуліну, лептину, кортикостерону, проводили аналіз варіабельності серцевого ритму. При проведенні дослідження було встановлено, що у самців щурів, які перенесли внутрішньоутробну гіпергліке¬мію, вже в препубертатному періоді спостерігалися порушення нейроендокринного балансу. При цьому у них на тлі еуглікемії натщесерце відзначалися гіперліпідемія, гіпертригліцеридемія, гіперхолестеринемія зі збільшенням рівня лептину, інсуліну та кортикостерону. Виявлені зрушення гормонального балансу і показників жирового обміну розвивалися одночасно зі змінами вегетативного балансу, який характеризувався переважанням його симпатичного компонента на фоні високої активності парасимпатичного відділу. Про це свідчило збільшення індексу LF/HF до 2,4 і спектральної потужності високочастотного компонента, що свідчить про активність парасимпатичної нервової системи, яка на 28% (p<0,05) була вищою, ніж у контрольних тварин. Встановлений факт існування нейроендокринного дисбалансу у нащадків самок з експериментальним гестаційним діабетом можна розглядати як важливий прогностичний показник формування метаболічних порушень ще в препубертатному періоді, маніфестацію яких можна буде спостерігати вже після періоду статевого дозрівання з прогресуванням виявлених змін до старості.
Хронічна гіперглікемія плода як предиктор формування нейроендокринного дисбалансу з метаболічними порушеннями
Хроническая гипергликемия плода как предиктор формирования нейроэндокринного дисбаланса с метаболическими нарушениями
Keywords: neuroendocrine balance; carbohydrate and lipid metabolism; metabolic disturbances; experimental gestational diabetes; нейроендокринний баланс; вуглеводний та жировий обмін; метаболічні порушення; експериментальний гестаційний діабет; нейроэндокринный баланс; углеводный и жировой обмен; метаболические нарушения; экспериментальный гестационный диабет